2012
DOI: 10.1007/s00405-012-2139-8
|View full text |Cite
|
Sign up to set email alerts
|

Cost-minimisation and cost-effectiveness analysis comparing transoral CO2 laser cordectomy, laryngofissure cordectomy and radiotherapy for the treatment of T1–2, N0, M0 glottic carcinoma

Abstract: The financial costs of laryngeal cancer treatment are a notable burden on healthcare budgets. In this study, we assess whether CO2 laser surgery is cheaper than radiotherapy or laryngofissure and cordectomy in the treatment of T1-2, N0, M0 glottic squamous cell carcinoma. 56 patients with a mean age of 65.88 years (SD = 10.04), 53 men and 3 women, with T1-2, N0, M0 glottic squamous cell carcinoma were retrospectively analysed. We conducted a comparative analysis of costs associated with three treatments: carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 15 publications
0
30
0
2
Order By: Relevance
“…Studies assessing the costs of hospitalization in HNC have been conducted in Thailand [71], Spain [22], France [63], the UK [66], and the USA [33, 43, 56]. While it is not possible to compare these costs across different countries and healthcare systems, each study concluded that the burden of hospitalization costs is high.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies assessing the costs of hospitalization in HNC have been conducted in Thailand [71], Spain [22], France [63], the UK [66], and the USA [33, 43, 56]. While it is not possible to compare these costs across different countries and healthcare systems, each study concluded that the burden of hospitalization costs is high.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the authors attributed €138 million of this cost to the 26 % of HNC caused by HPV infections [63]. A retrospective study of patients treated for glottic cancer in Spain found that mean hospital costs per day were €600–700 (costing year NR) [22]. While the vast majority of database studies are done in Western countries, a study using national health data in Thailand reported that, in 2010, hospital charges totaled 691 million Thai baht (THB) (at the time, US$21.8 million), or THB26,556 (US$838) for each of the 26,012 admissions for diagnosis and treatment of HNC [71].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations